1995
DOI: 10.12693/aphyspola.87.325
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Luminescent Properties of ZnTe-Cd1-xMnxTe1-ySeyHeterojunction

Abstract: ZnTe-Cd1-xMnxTe1-ySey heterojunctions were prepared by vaportransport epitaxy of ZnTe on In-doped Cd1-xMnxTe1-ySey (x = 0.05, y = 0.03) single crystalline substrate in vacuum. At temperatures lower than 120 K the infrared and red electroluminescence were observed from the ZnTe-Cd1-xMnxTe1-ySey diode with forward current density in the range 0.003-4.0 A/cm2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Benzofuran (Figure , 68 ) has been used as a common probe molecule to evaluate catalyst performance in hydrodeoxygenation reactions, and various studies using Ni−Mo or Co−Mo catalysts have been reported, with the former being more active for this substrate. As indicated above, the reduced benzofuran derivative, 2,3-dihydrobenzofuran, resembles some of the cyclic ethers found in lignin and is therefore studied as a model compound of this linkage. Different hydrodeoxygenation routes have been suggested depending on the catalyst and conditions used, but ethylcyclohexane is commonly obtained as the major product.…”
Section: Catalytic Lignin Transformationsmentioning
confidence: 99%
“…Benzofuran (Figure , 68 ) has been used as a common probe molecule to evaluate catalyst performance in hydrodeoxygenation reactions, and various studies using Ni−Mo or Co−Mo catalysts have been reported, with the former being more active for this substrate. As indicated above, the reduced benzofuran derivative, 2,3-dihydrobenzofuran, resembles some of the cyclic ethers found in lignin and is therefore studied as a model compound of this linkage. Different hydrodeoxygenation routes have been suggested depending on the catalyst and conditions used, but ethylcyclohexane is commonly obtained as the major product.…”
Section: Catalytic Lignin Transformationsmentioning
confidence: 99%